Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-36
|View full text |Cite
|
Sign up to set email alerts
|

Hyperarticulation in short intonational phrases in three Australian languages

Abstract: In Lindblom's Hyper-and Hypo-articulation (H & H) theory, speech varies between clear and less clear depending on the communicative context. Hyperarticulation is known to reflect prosodic boundary information and prosodic prominence or focus. The realisation of hyperarticulation appears to differ between languages. In this study of three Australian languages, it is asked whether, in pre-boundary position in short prosodic phrases, vowel lengthening tends to co-occur with acoustic evidence of hyperarticulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Jepson and Stoakes (2015) also showed that consonants after phonemically short vowels have longer duration than consonants after phonemically long vowels. As is the case throughout the Australian Indigenous languages (see e.g., Butcher, 2006), the vowel space is compressed and centralised relative to the cardinal vowels in Djambarrpuyŋu, as is also observed in Gupapuyŋu (e.g., Graetzer et al, 2016).…”
Section: The Djambarrpuyŋu Languagementioning
confidence: 72%
See 2 more Smart Citations
“…Jepson and Stoakes (2015) also showed that consonants after phonemically short vowels have longer duration than consonants after phonemically long vowels. As is the case throughout the Australian Indigenous languages (see e.g., Butcher, 2006), the vowel space is compressed and centralised relative to the cardinal vowels in Djambarrpuyŋu, as is also observed in Gupapuyŋu (e.g., Graetzer et al, 2016).…”
Section: The Djambarrpuyŋu Languagementioning
confidence: 72%
“…By contrast, in Australian languages, vowels associated with an accentually prominent or lexically stressed syllable do not consistently lengthen compared to unaccented vowels. Evidence of stressed or accentual vowel lengthening has been found in Arrernte, a Pama-Nyungan language of Central Australia (Tabain, 2016); Pitjantjatjara, a Pama-Nyungan language of Central Australia (Tabain, Fletcher, & Butcher, 2014); and in varieties of Bininj Kunwok and Dalabon, two non-Pama-Nyungan languages spoken in Northern Australia (Fletcher & Evans, 2002), but not in Mawng, a non-Pama-Nyungan language of Northern Australia (Fletcher et al, 2015); Warlpiri a Pama-Nyungan language of Central Australia (Pentland, 2004); nor in preliminary studies of Djambarrpuyŋu (Jepson, Fletcher, & Stoakes, 2016), the language under investigation in this paper, or in Gupapuyŋu, a closely related language variety (Graetzer, Fletcher, & Hajek, 2016). There is also contrastive vowel length in some of these languages (Pitjantjatjara, Warlpiri, Djambarrpuyŋu, and Gupapuyŋu).…”
Section: Prosodic Lengthening Effects In Australian Languagesmentioning
confidence: 90%
See 1 more Smart Citation